PERAN WILYATUL HISBAH DALAM PENANGGULANGAN REMAJA TERHADAP FENOMENA IKHTILATH SEBAGAI PENGUATAN SYARI’AT ISLAM DI WILAYAH KOTA BANDA ACEH - dewi, ratna; lasri, Lasri; bariah, chairul; jasmadi, jasmadi; Maylisna M, Ira (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Wilayatul Hisbah is an official institution established by the government in Aceh Province. Its main task is to implement amar ma`ruf nahi mungkar. One of the duties of Wilayatul Hisbah is to supervise the implementation and violation of laws and regulations in the field of Islamic sharia, including in terms of supervising the association of teenagers in Banda Aceh City so as not to fall into things that violate Islamic sharia. The purpose of this study is to analyze the role of Wilayatul Hisbah in the prevention of adolescents against the phenomenon of ikhtilat in the Aceh region, as well as obstacles in the prevention of adolescents against the phenomenon of ikhitlat. In addition, it also evaluates the tasks carried out by Wilayatul Hisbah, namely supervising the implementation and violation of Islamic Sharia, providing guidance and spiritual advocacy for everyone who violates Islamic Sharia legislation based on existing evidence, when carrying out coaching tasks so that implementation is carried out in accordance with existing regulations. The research method used is a qualitative method, with data collection techniques of participatory observation, interviews (structured), and documentation, while the determination of the research sample is carried out by purposive sampling method. The results showed that Wilayatul Hisbah plays an important role in dealing with the phenomenon of ikhtilath among teenagers. In this case, Wilayatul Hisbah starts the step by giving early warnings to teenagers regarding ikhtilath behavior through a persuasive approach, providing an understanding of the negative impact on morality and social society. Furthermore, Wilayatul Hisbah carries out coaching for teenagers who are involved or at risk of being involved, focusing on religious and social approaches. This coaching aims to deepen teenagers' understanding of Islamic values and strengthen the morality of teenagers in Banda Aceh. It is hoped that this research will directly contribute to sustainable policies related to the Role of Wilayatul Hisbah in Countering Adolescents Against the Phenomenon of Ikhtilath in the Islamic Region of Aceh in Banda Aceh City